MarkeTrak 10: History and Methodology - Powers, Thomas A.; Rogin, Carole (Seminars in Hearing, 2020)
MarkeTrak has been conducted on a regular schedule for over 30 years to take the pulse of the hearing health care market and of consumers with hearing loss. The current version, MarkeTrak 10 (MT10), builds on the successful completion of MarkeTrak 9, with the same two objectives: to estimate hearing difficulty, hearing aid usage, and adoption of hearing aids in the United States and to gain insights into the consumer's journey through the hearing health care delivery system. In addition, MarkeTrak 10 added additional questions regarding use and satisfaction with Personal Sound Amplification Products (PSAPs) by both owners and nonowners of hearing aids.
Keywords: MarkeTrak; hearing aids; hearing difficulty